Penerapan Model Pembelajaran Tipe Card Sort untuk Meningkatkan Hasil Belajar Mata Pelajaran Sejarah di SMA N 1 Pangkalan Kerinci Tahun Ajaran 2022/2023 - Intan Ervan Fauzar; Bunari Bunari; Asril Asril (CHRONOLOGIA, 2022)
The background of this research is the low student learning outcomes in history subjects in class XI IPS 1 SMA Negeri 1 Pangkalan Kerinci. Based on these problems, the formulation of the research problem is how can the application of the Card Sort Type learning model improve student learning outcomes XI IPS 1 SMA Negeri 1 Pangkalan Kerinci. The method used in this research is classroom action research. The purpose of this study was to determine the activities of teachers and students in implementing the Card Sort Type learning model to determine the effect of this learning on XI IPS 1 students of SMA Negeri 1 Pangkalan Kerinci in history subjects. This research was conducted in two cycles in cycle 1 the learning outcomes achieved 52.38% classical completeness and increased in cycle 2 90.48%. Based on the research results, the Card Sort Type model has an influence on student learning outcomes XI IPS 1 SMA Negeri 1 Pangkalan Kerinci in history subjects.